2021
DOI: 10.1007/s11528-021-00665-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Students’ Perceptions of Screencasting Style of Video Feedback in Online Courses

Abstract: Feedback is an essential part of the learning process. Asynchronous online courses are marked by an abundance of text-based feedback. Yet, video feedback in asynchronous online courses is a nascent field of inquiry. This study investigated student perceptions of screencasting style of video feedback in online courses. During this course, students received video feedback from their instructor, and provided and received video feedback to their peers. A total of 84 graduate students completed an end-of-course sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…By 2015 the research had moved on to a student-focused frame of reference exemplified by Borup et al (2015, p. 1) and while their research did not find a statistically significant improvement in performance with video feedback vs text, it did show "affordances of video encouraged more supportive and conversational communication." Lowenthal et al (2021) still classify video feedback as being in its infancy. They state, "we have found that research, theory, and practice all suggest that video feedback is an instructional strategy online instructors can use to improve instructor presence" (p. 267).…”
Section: Video Delivery Feedback and The Online Learning Environmentmentioning
confidence: 99%
See 3 more Smart Citations
“…By 2015 the research had moved on to a student-focused frame of reference exemplified by Borup et al (2015, p. 1) and while their research did not find a statistically significant improvement in performance with video feedback vs text, it did show "affordances of video encouraged more supportive and conversational communication." Lowenthal et al (2021) still classify video feedback as being in its infancy. They state, "we have found that research, theory, and practice all suggest that video feedback is an instructional strategy online instructors can use to improve instructor presence" (p. 267).…”
Section: Video Delivery Feedback and The Online Learning Environmentmentioning
confidence: 99%
“…Kaltura (https://corp.kaltura.com/) offers the option for students to change between Screencast, Web camera, Screencast with Web camera inlay, Web camera with Screencast inlay and a side-byside option. See Lowenthal et al (2021) for an explanatory figure.…”
Section: Video Delivery Feedback and The Online Learning Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Videos, as tools of asynchronous e-learning in medical education, are not new entries, nor have they been studied a little. Video collections,[ 1 ] video feedback,[ 2 3 4 ] video effectiveness,[ 5 6 ] video groups[ 2 ] and multiple video comparisons[ 7 8 9 ] are some examples of the utilisation of video technology in e-learning. Videotaped e-lessons, however, introduce a new module of asynchronous e-learning, totally organised in terms of synchronous e-learning, from the beginning until the end of the semester, and have replaced educational procedures in classrooms due to the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%